PENGARUH IMPLEMENTASI KEBIJAKAN TERHADAP KEPUASAN MASYARAKAT MELALUI KUALITAS LAYANAN SEBAGAI VARIABEL INTERVENING PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN PENAJAM PASER UTARA - Dina Ryanti; Edy Wahyudi; Panca Oktawirani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the effect of policy implementation on public satisfaction, both directly and indirectly through service quality as an intervening variable, in population administration services in Penajam Paser Utara Regency. The study is motivated by the importance of improving public service quality, particularly in regions supporting the development of Indonesia’s New Capital City (IKN), which are experiencing significant development dynamics and demographic changes. This research employs a quantitative approach, with data collected through questionnaires distributed to users of population administration services. Data analysis was conducted using Structural Equation Modeling Partial Least Squares (SEM-PLS). The results indicate that policy implementation has a significant effect on service quality, policy implementation has a significant effect on public satisfaction, and service quality has a significant effect on public satisfaction. Furthermore, the indirect effect analysis demonstrates that service quality significantly and strongly mediates the relationship between policy implementation and public satisfaction. These findings suggest that effective policy implementation will be more successful in increasing public satisfaction when accompanied by improvements in service quality.